2023
DOI: 10.1111/ejh.13926
|View full text |Cite
|
Sign up to set email alerts
|

Global reported impacts of COVID‐19 on lymphoma patients and the emerging clinical management approaches in response to the ongoing pandemic

Abstract: The Coronavirus disease 2019 (COVID-19) pandemic has dramatically impacted the health risk and management of patients with lymphoma. Clinical evaluations on the impact of COVID-19 on lymphoma patients are currently limited however, reports have shown a correlation with specific variants and more severe COVID-19 complications and higher mortality rates relative to other disease states and age-matched populations. During peak pandemic periods this created a concerning management problem for clinicians and raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…This study included patients treated during the COVID-19 pandemic, which universally affected care and treatment of patients with lymphoma; we do not have previous registry data to compare outcomes of patients during the COVID-19 pandemic with historical cohort but this could be a factor contributing to compromised patient outcomes, particularly in resource-limited settings that were worse affected by the COVID-19 pandemic. 30 Our data also show that less than half of the relapsed patients were offered salvage treatment and an even lesser number proceeded to autologous bone marrow transplantation across both resource settings. Several reasons account for this low referral, including lack of finances, fewer centers offering high-dose salvage treatments, limited availability of novel drugs, and no center offering chimeric antigen receptor-T-cell (CAR T) treatment in the whole country.…”
Section: Discussionmentioning
confidence: 51%
“…This study included patients treated during the COVID-19 pandemic, which universally affected care and treatment of patients with lymphoma; we do not have previous registry data to compare outcomes of patients during the COVID-19 pandemic with historical cohort but this could be a factor contributing to compromised patient outcomes, particularly in resource-limited settings that were worse affected by the COVID-19 pandemic. 30 Our data also show that less than half of the relapsed patients were offered salvage treatment and an even lesser number proceeded to autologous bone marrow transplantation across both resource settings. Several reasons account for this low referral, including lack of finances, fewer centers offering high-dose salvage treatments, limited availability of novel drugs, and no center offering chimeric antigen receptor-T-cell (CAR T) treatment in the whole country.…”
Section: Discussionmentioning
confidence: 51%
“…Also, patients with lymphoma have compromised immune systems both due to the lymphoma itself and the immunosuppressive treatment. Several studies have reported a more severe COVID-19 trajectory among patients with lymphoma compared to the general population and also compared to patients with solid organ cancer [10,11].…”
Section: Introductionmentioning
confidence: 99%